Nomenclatural and morphological novelties in Tovomita laurina (Clusiaceae) - Engels, Mathias Erich; Marinho, Lucas Cardoso (Phytotaxa, 2018)
Tovomita Aublet (1775: 956) is a Neotropical genus with ca. 70 spp. Recent discoveries of new taxa displaying peculiarities in the leaves and fruits (Poncy & Offroy, 2006; Marinho et al., 2016) have increased the morphological variation within the genus. The fruits are historically neglected in the taxonomy of the group because most species have a common pattern of fruit morphology (i.e., spheroid or pyriform, smooth epicarp, red mesocarp, and orange aril). In addition, the ovary in Tovomita has four to six locules, but the intraspecific variation in the number of carpels has not been recorded, except for the T. weddelliana Planchon & Triana (1860: 277) species complex. During a field work in Teles Pires River, Mato Grosso state, Brazil, we found a remarkable population of T. laurina Planchon & Triana (1860: 282) that includes individuals with an unusual morphological variation in the fruits: five to seven carpels. Tovomita laurina was described only based on staminate plants, and the pistillate flower and fruits have not yet been described. Thus, we present a description of the reproductive whorls and fruits of T. laurina based on specimens from various locations and pictures of the living plant taken in situ. Additionally, we designate a lectotype and discuss the differences in the number of petals from the original description.